2014
DOI: 10.1080/02786826.2014.901488
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Comparison of Real-Time Measurement Methods for 10–100-nm Particle Size Distributions

Abstract: We present information regarding the relative performance of five TSI particle sizing instruments when presented with several log-normally distributed particle populations that vary in terms of composition, concentration, and modal mean diameter (in the range of 10-100 nm) in a controlled laboratory environment. In experiments conducted with NaCl, NaNO 3 , and organic aerosols, across a total particle concentration suite ranging from approximately 1 × 10 4 cm −3 to 1 × 10 6 cm −3 , total number concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…For particles in the 10-100 nm size range, Hornsby and Pryor (2014) report an agreement between several TSI SMPS systems and a TSI FMPS system (fast mobility particle sizer) of within ±30 % for particle number concentration and of within ±7.5 % for geometric mean diameter (D pg ). Those values can be considered a lower limit for the uncertainties in long-term field measurements, especially at locations with difficult maintenance conditions.…”
Section: Particle Number Size Distribution Measurementsmentioning
confidence: 86%
“…For particles in the 10-100 nm size range, Hornsby and Pryor (2014) report an agreement between several TSI SMPS systems and a TSI FMPS system (fast mobility particle sizer) of within ±30 % for particle number concentration and of within ±7.5 % for geometric mean diameter (D pg ). Those values can be considered a lower limit for the uncertainties in long-term field measurements, especially at locations with difficult maintenance conditions.…”
Section: Particle Number Size Distribution Measurementsmentioning
confidence: 86%
“…For example, although inter-comparison of the FMPS and SMPS data indicate Pearson correlation of hourly average total particle number concentration > 0.9, N nuc from the SMPS was systematically higher (Pryor et al, 2010), potentially leading to higher estimated J 6 . Lab inter-comparison of these instruments also indicate that, to a degree that is a function of composition, the SMPS exhibits higher modal peak concentrations and lower modal diameter than the FMPS (Hornsby and Pryor, 2014). Thus, the data sets from the two experimental campaigns are treated separately.…”
Section: Event Classification Growth Rates Formation Rates and Surmentioning
confidence: 99%
“…The study concluded that the agreement between FMPS and SMPS is linked to the particle size and morphology. Hornsby and Pryor (2014) compared four SMPS systems and one FMPS for particles with GMDs between 10 nm and 100 nm. They found low deviation for the FMPSs from the GMD ( §7.5%) as measured by the SMPS systems.…”
Section: Introductionmentioning
confidence: 99%